Bridging research and practice: developing beekeeping knowledge and innovation systems - Fabricius Kristiansen, Lotta; Ljung, Magnus; Blix Germundsson, Lisa; McCormick, Kes (Frontiers in Conservation Science, 2024)
This paper presents the concept of a Beekeeping Knowledge and Innovation System (B-KIS). This concept is closely related to the Agricultural Knowledge and Innovation System (AKIS) -both theoretically and methodologically. By adopting a B-KIS approach we can: a) depict the general structure and functioning of activities aiming for knowledge development, innovation and learning within the apicultural sector; b) improve understanding of how services for beekeepers are embedded into national B-KIS; and c) provide some conceptual elements to support the development of a national or regionally adapted communication strategy for improved sustainability of beekeeping. From a policy perspective, it is important that the B-KIS becomes integrated into the national strategic AKIS plans.